Calculations on a Class of Candidate Solutions for the Distortion Problem on l 2 - Sanacory, Frank (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
In 1994 E. Odell and Th. Schlumprecht showed that the Hilbert space (` 2 ) was arbitrarily distortable. However, we do not have a defined sequence of norms that would perform this distortion. G. An- droulakis and the author defined a class of norms equivalent to the Hilbert space norm. These norms are candidate sequences of norms that might distort ` 2 . These norms are recursively defined and calculations with these norms are quite difficult. Here we present a tool, a Python program, that calculates the norms defined by G. Androulakis and the author.